2003
DOI: 10.1161/01.cir.0000065578.00869.7c
|View full text |Cite
|
Sign up to set email alerts
|

Reinduction of Atrial Fibrillation Immediately After Termination of the Arrhythmia Is Mediated by Late Phase 3 Early Afterdepolarization–Induced Triggered Activity

Abstract: Background-Atrial fibrillation (AF) at times recurs immediately after termination of the arrhythmia. The mechanism (s) responsible for the extrasystole that reinduces AF is largely unknown. We hypothesized that abbreviation of action potential duration (APD) would permit very rapid rates of excitation, known to induce intracellular calcium loading, which in turn could promote delayed and/or early afterdepolarizations (EADs). Methods and Results-Acetylcholine (ACh, 1 mol/L) was used to abbreviate atrial APD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
228
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(246 citation statements)
references
References 19 publications
15
228
2
1
Order By: Relevance
“…A long preceding pause increases accumulation of intracellular Ca, leading to larger sarcoplasmic reticulum Ca release in the first beat after the pause. 3 This latter phenomenon, in addition to APD shortening induced by acetylcholine, contributes to the development of late phase 3 Ca i elevation. The combination of late phase 3 Ca i elevation and the hyperactive NCX current facilitates the development of focal discharge from the PVs in heart failure.…”
Section: Late Phase 3 Early Afterdepolarizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A long preceding pause increases accumulation of intracellular Ca, leading to larger sarcoplasmic reticulum Ca release in the first beat after the pause. 3 This latter phenomenon, in addition to APD shortening induced by acetylcholine, contributes to the development of late phase 3 Ca i elevation. The combination of late phase 3 Ca i elevation and the hyperactive NCX current facilitates the development of focal discharge from the PVs in heart failure.…”
Section: Late Phase 3 Early Afterdepolarizationsmentioning
confidence: 99%
“…Persistent Ca i elevation in phase 3 of the action potential may activate the NCX current and induce late phase 3 early afterdepolarizations. 3,4,9 These late phase 3 early afterdepolarizations initiate focal discharge and AF. We propose that this mechanism underlies the focal discharges observed in the present study.…”
Section: Late Phase 3 Early Afterdepolarizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation to this new situation results in profound changes in the ion channels controlling Ca 2+ reuptake and release by the sarcoplasmic reticulum 13,21 . These changes persist for some time after the restoration of a normal sinus rhythm (for example, after cardioversion), rendering the recurrence of AF more likely 58 . Increases in spontaneous electrical activity have been suggested to have a major role in abnormal intracellular Ca 2+ handling in the genesis of AF 59 .…”
Section: Altered Calcium Homeostasismentioning
confidence: 99%
“…Abnormal activity of the autonomic nerve could also induce AF by inducing cardiac intracellular calcium overload and early after depolarization (EAD). Burashnikov and Antzelevitch (2003) found that injecting Ach into the coronary artery could shorten the action potential of atrial muscle cells and cause rapid atrial pacemaking, which could easily induce AF. They also found that the sudden stop of AF or the increasing of the rapid pacemaking frequency could instantly improve the tension of atrial muscle cells, which would cause 3 phases of rapid EAD of action potential and extrasystole, which would induce AF.…”
Section: Discussionmentioning
confidence: 99%